IMPLEMENTATION OF VILLAGE CONSULTATIVE BODY FUNCTIONS IN MOTABANG VILLAGE, LOLAK DISTRICT, BOLAANG MONGONDOW REGENCY - Moh. Yusuf Ishak; Rabina Yunus; Indar Arifin (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This study aims to examine the implementation of the functions of the Village Consultative Body in Motabang Village, Lolak District, Bolaang Mongondow Regency. By using qualitative methods with a descriptive approach, this study aims to answer research questions effectively. The results showed that members of the Village Consultative Body in Motabang Village, Lolak District, Bolaang Mongondow Regency did not carry out their duties and functions optimally. Several factors contribute to this situation, such as the limited involvement of the Village Consultative Body in the formulation and drafting of Village Regulations, unfulfilled community aspirations, and challenges in monitoring the performance of the Village Consultative Body due to tight schedules and personal relationships between its members and the Village Head. As a result, the Village Consultative Body in Motabang Village, Lolak District, Bolaang Mongondow Regency faced limitations in fulfilling its obligations and responsibilities.